A study on the energy dissipation of several different CFRP-based targets completely penetrated by a high velocity projectile - Hazell, Paul J.; Appleby-Thomas, Gareth J. (Elsevier, 2009)
The threat of fragmenting munitions from MANPADS to civilian and military aircraft has, in recent years, become an ever increasing worry. One of the ways to enhance the protection of CFRP-based composites is to add lightweight materials that can provide increased ballistic protection. In this study, several hybrid CFRP laminates of different material and geometrical configurations have been subjected to impact by a high velocity steel sphere with an impact energy of c.a. 440 J. It was found that 12 layers of ballistic-grade Kevlar™ loosely bound to the rear of the CFRP laminate proved to be the most weight-efficient method of dissipating the kinetic energy of the projectile. Furthermore, the impact response of a non-woven symmetrical CFRP laminate has been compared to that of a woven laminate over an impact-energy regime of 92–459 J. At lower impact-energies there were strong indications that the non-woven laminate out-performed the woven laminate whereas at the higher impact-energies the ballistic performance was seen to be approximately the same.
Keywords: Airline safety; protection of airliners; MANPADS; Kevlar